Informe de pasantía cámara de industria y comercio colombo chilena “fortalecimiento comercial a empresas de Chile y Colombia” - Sánchez Rojas, Juan Manuel (Universidad Antonio Nariño, 2021)
This report reflects the different activities carried out in the last 6 months at the Colombo Chilean Chamber of Commerce and Industry, located in Bogotá. The Colombo Chilean Chamber is a non-profit trade union entity dedicated to promoting and strengthening trade relations and investments between Chilean and Colombian companies, it also provides advice on investment projects, market studies, export plans, organization of events, among others. The intern carried out his activities as a commercial professional, who is in charge of carrying out the commercial management of the different affiliated companies assigned at the beginning of the internship, management that includes the search for possible prospective companies for commercial approaches and creation of databases which They contain striking contact information for the internal search that each company has, and it also takes care of the other requirements that the companies or the Chamber itself may have. The topic of what Orus Data is and its management is also touched upon, such as searching for the contacts to feed this platform and using the tools created to improve this search. The purpose of the internship is to put into practice the knowledge acquired in academic training, which turned out to be useful during the internship process.